First Record of Stiliger smaragdinus Baba, 1949 (Mollusca: Sacoglossa: Limapontiidae) from India - Apte, D. A.; Kamboj, R. D.; Bhave, Vishal (Journal of the Bombay Natural History Society (JBNHS), 2015)
No Abstract.